Electrocoagulation of palm oil mill effluent using aluminium electrodes - Ab Aziz, Nur Adila
Electrocoagulation is a treatment ntethod that has the potential in removing various pollutants without generating secondary pollutants which only involves simple and coinpact equipment. In this study, the potential to treat palm oil mill eflnent using an electrocoagulatioiz process toas studied. The objectives of the study are to determine the optimlrm current density, the optimum retention time, and the optimuin initial pH of the sample for the electrocongul~tiono f palm oil mill effluent using aluminium in terms of renroving chemical oxygen demand, suspended solids and colour of the palm oil mill eflnent. The palm oil mill efluent samples were collectedfrom Pertubuhan Peladang Negeri Johor palm oil nrill. The range of current density, retention time and initial pH used to obtain the optimunr value were 20-100 Aim2 10-30 minirtes, and 2-10, respectively. T'he distance bettoeen the electrodes and settling time were kept constant at 5 cm and 30 minutes, respectively. The sludge volrinle and the variability of pH changes throughout the electrocoagulation p~ocess zuere also studied.Results show that the optimunz conditions for the electrocoagulation process using nlumiitiirnl-altrminium electrode pair are current density of 80 Aiin2, retention time of 15 minutes, and initial pH of 4. This optimum condition was able to reduce chemical oxygen demand, suspended solids,nnd colour up to 72.75%, 96.93% and 92.79%, respectively. At the end of electrocoagulntion, the sludge volllnle obtained rum 27.27% and pH was increasedfroin 4.00 to 4.38. It can be concluded that the electrocoagulation process has the potential to be utilized for efective removal of cheinical oxygen demand, suspended solids and colour of the palm oil mill effluent.